Development of Fiber-Optic Based Pressure Sensor Insole System for Gait Analysis - Mazlan, Nur Nadiah; Wan Zaki, Wan Suhaimizan (Evolution in Electrical and Electronic Engineering, 2024)
This project addresses the important need for precise and accessible gait subphase detection and dynamic balance evaluation methodologies, particularly for those with neurological illnesses and mobility limitations. The current gait analysis tool landscape provides hurdles, with older approaches being expensive and limited, and wearable sensors having constraints such as high costs and the requirement for recalibration. In response, the goal of this study is to create a Balance Assessment Through Fiber Optic-Based Pressure Sensor Insole Development for Gait Analysis, that reliably evaluates gait subphases and quantifies dynamic balance during human locomotion. Using plastic optical fibre (POF) technology, six fibre optic pressure sensors are embedded at crucial points on the insole. For real-time signal processing and analysis, the sensors are integrated with a data collecting system comprised of Arduino, NodeMCU, and MATLAB. The prototype testing results show consistent voltage outputs in the hindfoot area, averaging 0.06V, and in the forefoot area, averaging 0.10V. These results demonstrate the system’s capability to detect pressure changes accurately. These results not only validate the efficacy of the developed technology but also pave the way for enhanced understanding of gait dynamics, potentially leading to improved rehabilitation strategies and assistive technologies tailored to individual gait patterns and balance needs. The project’s findings will improve understanding of gait dynamics, opening the path for better rehabilitation programs and assistive technologies.